Export Instability and the External Balance in Developing Countries - Ghosh, Atish (IMF Working Papers; Working Paper ;, 1994)
Uncertainty about the export earnings accruing to a country (sometimes referred to as export instability) is an important source of macroeconomic uncertainty in many developing countries. Theory predicts that countries should react to increases in this form of uncertainty by increasing their level of savings. The resulting asset accumulations would then act as the country's insurance against the greater riskiness in its income stream. The paper tests this implication for a large sample of developing countries. In general, the results suggest that developing countries have indeed responded to increases in export instability by building up precautionary savings balances.